States in crisis, exacerbation of ethnic-social conflicts in Latin America, 1980-2016 (Quinto Sol, 2017)
Text of the keynote address by Jorge Pinto Rodriguez delivered in the Second International Congress "The indigenous peoples of Latin America. Advances, perspectives and challenges". Santa Rosa, La Pampa, September 2016.
Keywords: state; social conflict; indigenous peoples